Comparison Study of Bacterial Profile, Wound Healing, and Cost Effectiveness in Pressure Injury Patients Using Treatment Honey Dressing and Hydrogel - Putri, Nandita Melati; Margareta Lumbuun, Ruth Fitri; Kreshanti, Prasetyanugraheni; Saharman, Yulia Rosa; Tunjung, Narottama (Lingkar Studi Bedah Plastik Foundation, 2022)
Background : Pressure injury is a localized soft tissue injury caused by prolonged pressure over bony prominence. Most published papers used Manuka honey as dressing, while this product is expensive. As this reason, this study will use local product honey called Nusantara honey, to prove the use of local honey has better healing process, bacterial profile, and cost effectiveness, compared to the standard dressing, hydrogel.Method : This is a one-month experimental study conducted in patients with pressure injury that referred to our division. Parameter of the bacterial profile was taken from deep-tissue specimen. The healing process was examined with Pressure Ulcer Scale for Healing (PUSH) Tool. Cost was accumulated after all the treatment. Data was analysed with t-Test or Mann Whitney (if the distribution is not normal), with statistical significance was define as p<0.05..Result : Of 26 wounds, 12 were randomized to hydrogel and 14 to honey dressing. Characteristics were determined by sex, age, body mass index, level of consciousness, mobilization status, immobilization etiology, comorbidities, grade and location of ulcer, hemoglobin, leukocytes, and albumin level. There was clinically significant wound size reduction in honey dressing according to PUSH Tool (p=0.118). The bacterial profile and reduction were similar. Honey dressing appeared to be more cost effective in terms of dressing cost (p<0.001) and lower total cost.Conclusion: The local honey dressing has better wound healing outcome, although it is not statistically significant. Its capability of decreasing pathogens is similar with hydrogel, with lower cost, particularly the dressing cost. This local honey dressing could be a good choice as wound dressing in areas where the modern dressings are not available.